Exporting and innovating among emerging market firms: The moderating role of institutional development - Xie, Zhenzhen; Li, Jiatao (Journal of International Business Studies, 2018)
Building on the recombinatory view of innovation and an institutional perspective, this study investigated how the level of institutional development in a firm’s home region and the institutional distance between the home and export markets might influence the effectiveness of learning through exporting. For exporters in emerging economies, more support for R&D and better-developed market intermediaries at home were found to enhance the positive effect of exporting on firms’ innovation, while market openness in the home region tends to dampen it. Exporters exporting more to other emerging economies tend to be more innovative than those exporting more to advanced markets. These findings arise from an empirical study of exporting and innovation among Chinese manufacturers.